ANALYSES ON EXPRESSION OF INTERROGATIVE CONSTRUCTIONS IN LINGUISTICS - Yuldosheva Oyshajon Ruzmatovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. Analysis of studies of interrogative constructions in Uzbek linguistics was enlarged upon in this article. Also, citations were given from investigations of Russian linguist scientists to express attitude towards their opinions.